2022
DOI: 10.3926/jotse.1621
|View full text |Cite
|
Sign up to set email alerts
|

Prospective teachers' design of STEAM learning units: STEAM capabilities' analysis

Abstract: STEM education is a new field within which understandings of what constitutes effective practice, and how this can be supported, are still in their infancy. The present research describes the experiences of prospective elementary school teachers in designing collaboratively STEM activities. This designing experiences occurred in a context of a PD program called "Introduction to STEM education". During the STEM PD program, the pre-service teachers worked in six groups. Each group included three pre-service teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…These findings are similar to those from previous studies (Lee & Perret, 2022;Anabousy & Daher, 2022) in that they all report LbD as helpful in training teachers to integrate technology in the classrooms. However, unlike the previous studies, the present studies focused on the 6E LbD model for supporting teachers to integrate AI in the classrooms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are similar to those from previous studies (Lee & Perret, 2022;Anabousy & Daher, 2022) in that they all report LbD as helpful in training teachers to integrate technology in the classrooms. However, unlike the previous studies, the present studies focused on the 6E LbD model for supporting teachers to integrate AI in the classrooms.…”
Section: Discussionsupporting
confidence: 90%
“…They report that teachers highly rated the project as valuable to their learning. Also, Anabousy and Daher (2022) observed an improvement in skills for designing STEM learning units among preservice teachers who were involved in LbD training in Israel. In addition, Haas et al (2021) reported that hands-on activities helped pre-service teachers develop skills for facilitating Outdoor STEAM activities in the classroom.…”
Section: The Application Of Learning By Design Models In Technologica...mentioning
confidence: 90%
“…(3) interdisciplinarity, their goals and values remain unchanged. This coincides with the philosophy of STEAM (Haider, 1990;Marshall, 2014;Liao, 2016;MacDonald et al, 2019;Malele and Ramaboka, 2020;Anabousy and Daher, 2022).…”
Section: Introductionsupporting
confidence: 86%
“…Recently, the academic community has been interested in the concept, scope, and core theory of STEM and STEAM, and these successive publications provide strong theoretical support (Babaci-Wilhite, 2018;Culén and Gasparini, 2018;Milner-Bolotin, 2018;Khine and Areepattamannil, 2019;Videla et al, 2021;Anabousy and Daher, 2022). We live in a designed world.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the current research has highlighted the ability of in-service educators to integrate PBL and STEM [12,17]; however, research into pre-service teachers' (PSTs') ability to develop meaningful interdisciplinary, project-based STEM curricula is lacking. Research also suggests that teacher education programs fail to train PSTs for diverse classrooms or prepare them to integrate global awareness through social justice issues [25,35]. A gap exists between theory and classroom approaches related to integrating social justice theory with STEM practices [36].…”
Section: Pst's Abilities To Produce Pbl Stem Curricular Unitsmentioning
confidence: 99%